Analysis of Students' Questioning Skills During Discovery Learning: A Descriptive Study Based on The Revised Bloom's Taxonomy Framework - Safitri, Salsya Diva; Liliawati, Winny; Suyana, Iyon (Jurnal Penelitian Pembelajaran Fisika, 2024)
The problem in this study is the lack of questioning skills based on cognitive process dimensions and knowledge dimensions. This research aims to analyze questioning skills through students' written work using the revised Bloom's Taxonomy framework, specifically the cognitive process and knowledge dimensions. The participants were 32 students (15 males and 17 females) from class XI MIPA 3 at a high school in Bandung. This descriptive study employed documentation analysis using Google Forms for individual questions and worksheets for group questions. The results depict students' cognitive processes at the levels of remembering, understanding, applying, analyzing, evaluating, and creating as 18.25%, 47.44%, 9.49%, 18.25%, 2.92%, and 3.65%, respectively. In terms of knowledge dimensions, the percentages for factual, conceptual, procedural, and metacognitive knowledge were 24.82%, 72.99%, 2.19%, and 0%, respectively. It can be concluded that questioning based on cognitive processes is distributed across all levels from remembering to creating, while questions based on knowledge dimensions are predominantly conceptual.